Communicating Racism: A Study of Racial Microaggressions in a Southern University and the Local Community. Issue 2 (15th March 2019) - Harris, Tina M.; Janovec, Anastacia; Murray, Steven; Gubbala, Sneha; Robinson, Aspen
ABSTRACT: The current study was conducted with the goal of identifying specific communication behaviors – both verbal and nonverbal – that SOC at a PWI consciously and subconsciously identify as either an RMA or a contributing factor to the likelihood of one occurring. The experiences and voices of multiracial college students privileged over those of monoracial students in an effort to inspire institutional change and resist systemic oppression in its most basic form. The findings are consistent RMA research, while also introducing new categories and concepts that contribute to how scholars and SOC are "naming, detailing and classifying the actual manifestations of aversive racism". The students in this study experienced and reported on RMA they are experiencing both at the university and in the local community, which is consistent with previous research. Regardless of their race/ethnicity, these SOC experienced verbal and nonverbal RMA on a daily basis. These findings further demonstrate that communication is at the center of understanding RMA, as evidenced by the seven categories of communication responses and 30 corresponding concepts that are new to RMA scholarship.